Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Konsumen Pada Makanan Cepat Saji Mc.Donald’s Kota Bengkulu - Rustawati Rustawati; Suswati Nasution; Rina Trisna Yanti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the influence of cultural factors, social factors, personal factors and psychological factors on consumer purchasing decisions at Mc.Donald's fast food in Bengkulu City. This research is a quantitative research using 90 respondents. The data collection tool uses a questionnaire, the analytical method used is multiple linear regression, with validity test, reliability test, coefficient of determination and hypothesis testing using t test and f test. Multiple regression results show the equation Y = 1.814 + 0.183X1 + 0.231 X2 + 0.293X3 + 0.177X4 The resulting regression direction is positive, meaning that the more cultural, social and personal and psychological variables increase, the purchasing decision will also increase. The value of the coefficient of determination is 0.730. This means that X1 (cultural), X2 (social), X3 (personal) and X4 (Psychological) have an influence on purchasing decisions (Y) by 53.2% while the remaining 46.8% is influenced by other variables that are not investigated in this study. Overall, the results of the t test have a significant value less than 0.05, so it can be interpreted that X1 (culture), X2 (social), X3 (personal) X4 (Psychological) have a positive and significant influence on purchasing decisions (Y) either partially or simultaneously